Pengaruh Penggunaan Metode Pembayaran QRIS Terhadap Keputusan Pembelian Mahasiswa ITS: Studi Kasus Kantin Pusat ITS - Arvin Azmi Sava; Kentaro Mas'ud Mizoguchi; Rudi Aldo Hardika; Rifqi Naufal Luthfyardy; Nur Aini Rakhmawati (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This study aims to identify and analyze the effect of using the QRIS payment method on purchasing decisions in terms of three perceptions, namely the perceived effectiveness, convenience, and security of the QRIS payment method. This research uses a casual study methodology, which is a type of research to identify cause-and-effect correlations between two or more variables. In this study, data was collected randomly through questionnaires distributed via whatsapp social media to ITS students. Then, the data from the questionnaire was analyzed using multiple linear regression methods. The results of the analysis of this study indicate that together (simultaneously), the perceived effectiveness, convenience, and security of the QRIS payment method have a significant influence on purchasing decisions for students at the ITS Central Canteen. However, when viewed individually (partially) it is found that only the perception of convenience has a significant effect on purchasing decisions, while perceived effectiveness and perceived security do not have a significant effect on purchasing decisions for students at the ITS Central Canteen.